Nontraditional configuration of tuned liquid column damper inerter for base-isolated structures. (May 2023) - Masnata, Chiara; Di Matteo, Alberto; Adam, Christoph; Pirrotta, Antonina
Abstract: In this paper, the concept of a novel passive control device, namely the Nontraditional Tuned Liquid Column Damper Inerter (NT-TLCDI), is investigated in combination with seismic base isolation (BI), to control lateral displacement demands in base-isolated structures during seismic events. The considered NT-TLCDI is a revision of the ordinary configuration of the recently proposed Tuned Liquid Column Damper Inerter (TLCDI). Unlike the traditional TLCDI layout, which involves a secondary liquid mass in a U-shaped tank coupled with a grounded inerter and connected to the isolation system by a spring-dashpot system, in the NT-TLCDI configuration, the damper is in parallel with the inerter rather than the spring. The optimal design, including the determination of the tuning frequency and damping ratios of the NT-TLCDI, is discussed with the purpose to reduce the base displacement variance of the BI system assuming a white noise base excitation. Under the optimal tuning condition, it is found that the proposed NT-TLCDI provides a larger suppression of vibration amplitude of the BI system than the traditional TLCDI in both the frequency domain and time domain. A more interesting aspect is the reduction of the device displacement achieved by the NT-TLCDI, which may be beneficial in practice when the space for housing the device is limited.